We Go on a Train - Mattern, Joanne, 1963- (Egremont, MA : Red Chair Press, 2020)
"What to expect from a trip on a train"--Provided by publisher.
Includes index
Keywords: Railroad trains -- Juvenile literature; Transportation -- Juvenile literature